Effectiveness Use of Tiktok Social Media @DitjenPajakRI Deployment Information Taxation - Azullah Zamzam; Sri Hastjarjo; Yulius Slamet (PT FORMOSA CENDEKIA GLOBAL, 2023)
Public Relations Directorate General Tax (DGT) has role alone as extension worker tax. For increase awareness about information taxation to society. DJP Public Relations Using TikTok for educate public about taxation, mandatory tax Even though the TikTok @DitjenPajakRI had popular, however No Can last long because complicated TikTok algorithm. So, using TikTok requires a communication strategy special. Objective from study This is For describe the Directorate General of Public Relations communication strategy tax using the social media TikTok. Study This use method qualitative descriptive and interview as well as technique Documentation data collection. Research results This show that DGT Public Relations implemented the strategy communicate with appropriate with download and use content form short Language light and atypical.